Joel, Obadiah, Habakkuk and Zephaniah : an introduction and study guide - Hadjiev, Tchavdar S. (Tchavdar Stoyanov), 1971- (T & T Clark, 2020)
"Tchavdar S. Hadjiev introduces students to the books of Joel, Obadiah, Habakkuk, and Zephaniah (the Minor Prophets) in their original historical contexts and to the issues surrounding their composition and interpretation. Hadjiev pays particular attention to important topics such as eschatology, prophecy and cult, intertextuality, theodicy and the genre of the prophetic book. Readers will come to grips with the key themes of judgment, repentance, and salvation in relation to their historical and canonical contexts. Finally, Hadjiev provides a theological evaluation of the prophetic attitude to foreigners and the vision of their final destruction, which is pervasive in Joel, Obadiah, Habakkuk and Zephaniah, and helps readers to grapple with this theme in a modern context."-- Provided by publisher
The date and profile of Zephaniah's activity
Keywords: Bible. -- Joel -- Introductions.; Bible. -- Obadiah -- Introductions.; Bible. -- Habakkuk -- Introductions.; Bible. -- Zechariah -- Introductions.; Bible. -- Habakkuk; Bible. -- Joel; Bible. -- Obadiah; Bible. -- Zechariah; Biblical studies & exegesis.; Religion -- Biblical Studies -- Prophecy.; Introductions